2013
DOI: 10.1021/jp405683s
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the Hofmeister Series: Specific Ion Effects on Peptides

Abstract: Ion-specific effects on salting-in and salting-out of proteins, protein denaturation, as well as enzymatic activity are typically rationalized in terms of the Hofmeister series. Here, we demonstrate by means of NMR spectroscopy and molecular dynamics simulations that the traditional explanation of the Hofmeister ordering of ions in terms of their bulk hydration properties is inadequate. Using triglycine as a model system, we show that the Hofmeister series for anions changes from a direct to a reversed series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
206
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(232 citation statements)
references
References 40 publications
20
206
2
Order By: Relevance
“…The fact that anion binding in water can be affected without complete desolvation – even in the absence of traditionally strong supramolecular motifs for anion recognition – suggests an alternative approach to this difficult task. Moreover, these results dovetail with what is known about anions at the air-water interface 31 and the macromolecule-water interface, 32 and regarding the latter, point to other ways than cation-anion or hydrogen bonding that anions can interact with proteins.…”
supporting
confidence: 74%
“…The fact that anion binding in water can be affected without complete desolvation – even in the absence of traditionally strong supramolecular motifs for anion recognition – suggests an alternative approach to this difficult task. Moreover, these results dovetail with what is known about anions at the air-water interface 31 and the macromolecule-water interface, 32 and regarding the latter, point to other ways than cation-anion or hydrogen bonding that anions can interact with proteins.…”
supporting
confidence: 74%
“…The present results thus strongly indicate that Nandi and Robinson 6 actually did not succeed in capping the C -terminus. This observation, supported by the experimental fact that we were also unable to effectively cap the C -terminus of GGG by their esterification procedure (but instead had to use another synthetic route), 8 has important implications for molecular interpretations of the Hofmeister ordering of ions, as discussed below.…”
mentioning
confidence: 63%
“…However, we have found recently that while the N -terminus can be easily acetylated, it is actually rather difficult to cap the C -terminus of oligoglycines. 8 As a matter of fact, we were not able to effectively cap the C -terminus by the esterification procedure described in Ref. 6.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…11 Interactions may be better understood through simulations such as molecular dynamics which can probe equilibrium interactions. 12,13,14 However, there is no guarantee that these modelled interactions apply broadly to specific ion effects. Recently, it has been suggested that non-electrostatic ion-specific dispersion forces between solute and ion play a vital role in understanding Hofmeister effects.…”
Section: Introductionmentioning
confidence: 99%